An early view of the barriers to entry and career development in Building Engineering - Infante-Perea, Margarita; Román-Onsalo, Marisa; Navarro-Astor, Elena (DYNA, 2015)
The construction sector plays an important role in the global economy since it generates approximately 10% of the world GDP and employs around 7% of the workforce. Professional profiles for building engineers and barriers they may encounter when accessing the labor market as well as in their career development in the sector are researched. Having identified some variables as relevant barriers, this empirical research is exploratory in nature and adopts a descriptive and inferential approach, in order to analyze the influence of gender in the perception of barriers in two Spanish universities. Results show more difficult working circumstances for women, which allows us to reflect on the consequences of these early perceptions on the career development of the next generation of both male and female building engineers.